Study of Morphological Characteristics of Pollen Grains of Aronia mitschurinii A.K. Skvortsov & Maitul. - Grygorieva, Olga; Klymenko, Svitlana; Vinogradova, Yulia; Motyleva, Svetlana; Gurnenko, Ivan; Piórecki, Narcyz; Brindza, Ján (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2018)
Morphology of pollen grain was described for nine Aronia mitschurinii A.K. Skvortsov & Maitul. phenotypes (AM-01 – AM-09) at the laboratory of Department of Tropical and Subtropical plants of M.M. Gryshko National Botanical Garden of NAS of Ukraine (Kyiv) and Institute of Biodiversity Conservation and Biosafety at Slovak University of Agriculture in Nitra using an electron microscope Carl Zeiss LS 15. The measurement of morphometric parameters was carried out on 50 pollen grains from each phenotype using the AxioVision Rel. 4.8.2.0 program. The measurements were made in micrometer (μm). The length of polar axis (P) and the equatorial diameter (E) of grain, P/E ratio were measured and their variation was compared among studied genotypes. SEM investigations showed that the pollen grains are radial-symmetrical, isopolar, oblong-ellipsoid and 3- and 4-colporate. Texture is sinuous-tuberculate in equatorial zone and finely bumpy in polar zone. The polar axis and equatorial diameter of pollen grains values were varied from 34.16 to 50.14 μm and from 16.10 μm to 25.71 μm, respectively. This study showed that there were differences among the phenotypes in all measured factors. It is known that phenotypic variability is an evolutionarily fixed response of any group of organisms with a constant genotype to changes in environmental conditions and it is adaptive. Therefore, our research suggests that all individuals forming the introduction population of Aronia mitschurinii are sufficiently adapted to the conditions of M.M. Gryshko National Botanical Garden of NAS of Ukraine.